Autocrine Action of Thrombospondin‐2 Determines the Chondrogenic Differentiation Potential and Suppresses Hypertrophic Maturation of Human Umbilical Cord Blood‐Derived Mesenchymal Stem Cells. (25th August 2015) - Jeong, Sang Young; Ha, Jueun; Lee, Miyoung; Jin, Hye Jin; Kim, Dong Hyun; Choi, Soo Jin; Oh, Wonil; Yang, Yoon Sun; Kim, Jae‐Sung; Kim, Byung‐Gyu; Chang, Jeong Ho; Cho, Dong‐Hyung; et al.
Abstract: Previous studies have shown that mesenchymal stem cell (MSC)‐based therapies have varying efficacies for the treatment of various diseases, including cartilage defects. In this study, we demonstrated that the chondrogenic differentiation potential of human umbilical cord blood‐derived MSCs (hUCB‐MSCs) obtained from different individual donors varies, and we investigated the molecular basis for this variation. Microarray gene expression analysis identified thrombospondin‐2 ( TSP2 ) as a candidate gene underlying the interindividual variation in the chondrogenic differentiation potential of hUCB‐MSCs. To assess the association between TSP‐2 and the differentiation potential, we evaluated chondrogenic differentiation of hUCB‐MSCs treated with TSP2 siRNA. In addition, we studied the effect of supplementing exogenous recombinant TSP‐2 on TSP2 siRNA‐treated hUCB‐MSCs. We found that TSP‐2 autocrinally promoted chondrogenic differentiation of hUCB‐MSCs via the Notch signaling pathway, which was confirmed in MSCs from other sources such as bone marrow and adipose tissue. Interestingly, we observed that TSP‐2 attenuated hypertrophy, which inevitably occurs during chondrogenic differentiation of hUCB‐MSCs. Our findings indicated that the variable chondrogenic differentiation potential of MSCs obtained from different donors is influenced by the TSP‐2 level in the differentiating cells. Thus, the TSP‐2 level can be used as a marker to select MSCs with superior chondrogenic differentiation potential for use in cartilage regeneration therapy. Stem Cells   2015;33:3291–3303